Combination Chemotherapy of Lung Cancer – Co-Delivery of Docetaxel Prodrug and Cisplatin Using Aptamer-Decorated Lipid–Polymer Hybrid Nanoparticles - Wu R; Zhang Z; Wang B; Chen G; Zhang Y; Deng H; Tang Z; Mao J; Wang L (Dove Medical Press, 2020)
Ruifeng Wu,1,* Zhiqiang Zhang,1,* Baohua Wang,2 Ge Chen,3 Yaozhong Zhang,3 Haowen Deng,3 Zilong Tang,3 Junjie Mao,3 Lei Wang3 1Department of Thoracic Surgery, Baoding No.1 Central Hospital, Baoding, Hebei Province, People’s Republic of China; 2Department of Thoracic Surgery, The Second Hospital of Hebei Medical University, Shijiazhuang, Hebei Province, People’s Republic of China; 3Department of Thoracic Surgery, Fourth Hospital of Hebei Medical University, Tumor Hospital of Hebei Province, Shijiazhuang, Hebei Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lei Wang Email wangleihmu@protonmail.comPurpose: Lung cancer is the leading cause of cancer mortality worldwide. Drug resistance is the major barrier for the treatment of non-small cell lung cancer (NSCLC). The aim of this research is to develop an aptamer-decorated hybrid nanoparticle for the co-delivery of docetaxel prodrug (DTXp) and cisplatin (DDP) and to treat lung cancer.Materials and Methods: Aptamer-conjugated lipid–polymer ligands and redox-sensitive docetaxel prodrug were synthesized. DTXp and DDP were loaded into the lipid–polymer hybrid nanoparticles (LPHNs). The targeted efficiency of aptamer-decorated, DTXp and DDP co-encapsulated LPHNs (APT-DTXp/DDP-LPHNs) was determined by performing a cell uptake assay by flow cytometry-based analysis. In vivo biodistribution and anticancer efficiency of APT-DTXp/DDP-LPHNs were evaluated on NSCLC-bearing mice xenograft.Results: APT-DTXp/DDP-LPHNs had a particle size of 213.5 ± 5.3 nm, with a zeta potential of 15.9 ± 1.9 mV. APT-DTXp/DDP-LPHNs exhibited a significantly enhanced cytotoxicity (drug concentration causing 50% inhibition was 0.71 ± 0.09 μg/mL), synergy antitumor effect (combination index was 0.62), and profound tumor inhibition ability (tumor inhibition ratio of 81.4%) compared with the non-aptamer-decorated LPHNs and single drug-loaded LPHNs.Conclusion: Since the synergistic effect of the drugs was found in this system, it would have great potential to inhibit lung tumor cells and in vivo tumor growth.Keywords: lung cancer, combination therapy, docetaxel prodrug, cisplatin, aptamer-decorated, lipid–polymer hybrid nanoparticles